Modifying the Mini-Cog to Screen for Cognitive Impairment in Nonliterate Individuals. (17th August 2021) - Adhikari, Shambhu P.; Dev, Rubee; Borson, Soo
Abstract : Objectives . The Mini-Cog, a rapid, valid, and reliable screening tool for cognitive impairment, consists of 3-word recall and an executive clock drawing test (CDT). However, CDT requires at least basic literacy and cultural exposure to analog clocks, conditions not met in many population groups around the world. We developed a modification of the Mini-Cog (MMC) for use with nonliterate and literate individuals. Methods . Participants were adults (≥60 years) with no neurological diagnosis, with known cognitive impairment due to stroke, Parkinsonism, traumatic brain injury, or Alzheimer's disease, and whose family members were able to read and write. We replaced the CDT with two tasks of everyday life: a serial subtraction task or a multistep performance task. Family members rated the acceptability and feasibility of the Mini-Cog versions using a 6-point scale and completed a proxy-rated cognitive staging tool, the Dementia Severity Rating Scale (DSRS). Spearman's rho, Mann-Whitney U, and chi-square tests were used to evaluate group differences and associations between measures. Results . Data were collected from 63 participants (75 % ≥ 60   years, 67% nonliterate). Literacy was associated with CDT (chi-square strength 0.9, p < 0.001 ). Both MMC versions correlated with DSRS in healthy adults and patients (rho 0.6-0.7, p < 0.05 ). In literate individuals, the acceptability and feasibility of CDT and both alternate distractors were similarly high (5/6). Conclusions . Two alternate distractor tasks may successfully replace CDT in the Mini-Cog. The MMC versions are promising and deserve further study as screening tools for cognitive impairment in larger and more fully characterized samples.